Beyond sleep duration: protocol for a systematic review of multidimensional sleep health in relation to cardiovascular disease and mortality - Kobayashi Frisk, Mio; Lisik, Daniil; Zou, Ding (Frontiers in Sleep, 2024)
Adequate sleep duration has recently been recognized as a major determinant of cardiovascular health by the American Heart Association. This is a significant step towards recognizing sleep as a major lifestyle factor and pillar of health, along with physical activity and nutrition. However, healthy sleep is not only a matter of duration. Other dimensions, such as timing, regularity, efficiency, satisfaction with sleep, and daytime alertness are also deemed important to consider.We have designed a systematic review protocol according to the PRISMA-P guidelines with the objective of determining which sleep dimensions are predictors of all-cause mortality and major adverse cardiovascular events (MACE; cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and unstable angina requiring hospitalization), and whether or not the use of multiple dimensions of sleep yields superior predictive value to the use of sleep duration alone in predicting the above-mentioned outcomes.We will implement a systematic search strategy in 10 databases with independent manual screening by two reviewers. The aim is to comprehensively identify longitudinal studies which have examined the relationship between sleep duration and at least one other dimension of sleep and mortality or MACE. Meta-analysis will be performed after data extraction to address these objectives quantitatively.We anticipate that several sleep dimensions beyond sleep duration have been studied in relationship to all-cause mortality and MACE, and that a combination of multiple sleep dimensions can better predict these outcomes than sleep duration alone. Such findings would lay important groundwork to establish multidimensional sleep health as a major determinant of cardiovascular health.